First report of yellow rust ( Puccinia striiformis f. sp. tritici ) in wheat ( Triticum aestivum ) in Paraguay - Fernández Gamarra, Marta Alicia; Chavez, Pedro; Cardozo Téllez, Lourdes Maria; Scholz, Ruth; Bobadilla, Nathalia; Vargas, Maria José; Talavera Stefani, Liliana; Enciso, Guillermo; Thach, Tine; Hovmøller, Mogens Støvring; Kohli, Man Mohan (Plant disease, 2023)
Wheat yellow (stripe) rust caused by Westend. f. sp. Eriks. ( ) is an important disease worldwide (Chen 2005; Afzal et al., 2007; Hovmøller et al. 2011). In Latin America, the disease has been reported in Argentina, Bolivia, Chile, Colombia, Ecuador, Peru, Brazil, and Uruguay (van Beuningen and Kohli, 1986; German et al., 2007). The disease was observed for the first time in Paraguay at Capitán Miranda (Itapúa) (27°12'07.5888''S, 55°47'20.3640''W) in an environment with average minimum temperature below 10°C in July 2021 (coldest month). Symptoms were yellow rust pustules distributed linearly on the leaves of adult host plants (Fig. 1). Oval-shaped uredinia contained unicellular, yellow to orange, spherical urediniospores (28, 82 × 26, 83 μm), within the range reported by Rioux et al. (2015). Black telia produced yellow to orange teliospores (64, 12 × 15, 46 μm), which were within the range reported by Chen et al. (2014). All susceptible wheat cultivars had up to 100% disease severity. Ten- day-old seedlings of the susceptible cultivars were inoculated in a greenhouse using urediniospores collected from the field. Two weeks after inoculation, extensive sporulation was observed on the seedlings. For pathogen identification, DNA was extracted from wheat leaf segments containing urediniospores using the PureLink® Plant Total DNA Purification Kit (Invitrogen). PCR and sequencing were carried out by Macrogen (Korea), using the following species-specific primers: PSF (5`-GGATGTTGAGTGCTGCTGTAA-3`) / PSR (5`-TTGAGGTCTTAAGGTTAAAATTG-3`), which amplifies an internal transcribed spacer (ITS) region (Zhao et al. 2007); LidPs9 (TCGGTAAAACTGCACCAATACCT) / LidPs10 (TCCCAACAGTCCCCTTCTGT), which amplifies a fragment of the RNA polymerase II gene encoding the second largest subunit (rpb2); and LidPs11 (TTACGACATCTGCTTCCGCA) / LisPs12 (TGCGATGTCAACTCTGGGAC) and LidPs13 (TACGACATCTGCTTCCGCAC) / LidPs14 (GATTGCCCGGTATTGTTGGC), both pairs amplifying fragments of the β-tubulin 1 gene (tub1) (Kuzdraliński et al. 2017). The sequences obtained were OM631935, OM638432, OM718000, and OM718001 and were aligned using the GenBank BLAST tool (https://blast.ncbi.nlm.nih.gov/Blast.cgi), obtaining a 100% match with the following sequences: KC677574.1, KY411522.1, KY411533.1, and KY411542.1, respectively. Yellow-rust-infected leaf samples were collected from a field trial and sent to the Global Rust Reference Center (GRRC), Denmark. Simple sequence repeat (SSR) genotyping of samples from two different cultivars exhibited the genetic lineage PstS13 (www.wheatrust.org), which had previously been detected in South America (Carmona et al., 2019), thereby confirming the first report of wheat yellow rust in Paraguay. Considering that the Paraguayan wheat germplasm is highly susceptible to yellow rust, further studies are required to monitor potential spread and establishment of yellow rust in Paraguay and to explore potential sources of resistance to prevent future epidemics.